The impact of JNK inhibitor D-JNKI-1 in a murine model of chronic colitis induced by dextran sulfate sodium - Kersting S (Dove Medical Press, 2013)
Sabine Kersting,1* Volker Behrendt,1* Jonas Kersting,1 Kirstin Reinecke,3 Christoph Hilgert,1 Ingo Stricker,2 Thomas Herdegen,3 Monika S Janot,1 Waldemar Uhl,1 Ansgar M Chromik1 1Department of General and Visceral Surgery, St Josef Hospital, Ruhr University of Bochum, Bochum, Germany; 2Department of Pathology, Ruhr University of Bochum, Bochum, Germany; 3Institute of Experimental and Clinical Pharmacology, University Hospital of Schleswig-Holstein, Kiel, Germany *The two authors Sabine Kersting and Volker Behrendt contributed equally to this work Purpose: The c-Jun N-terminal kinases (JNK) are involved in the activation of T cells and the synthesis of proinflammatory cytokines. Several studies have established the relevance of the JNK pathway in inflammatory bowel diseases. The present study analyzed the therapeutic effect of D-JNKI-1, a specific JNK-inhibiting peptide, in a low-dose dextran sulfate sodium (DSS) model of chronic colitis. Methods: DSS colitis was induced in female C57/BL6 mice by cyclic administration using different concentrations of DSS (1.0% and 1.5%). Mice in the intervention groups received subcutaneous administration of 1 µg/kg D-JNKI-1 on days 2, 12, and 22. They were monitored daily to assess the severity of colitis, body weight, stool consistency, and the occurrence of occult blood or gross rectal bleeding using evaluation of the disease activity index. The animals were sacrificed after 30 days, and the inflamed intestine was histologically evaluated using a crypt damage score. Immunohistochemical quantification of CD4+ and CD8+ cells was also carried out. Results: Administration of 1 µg/kg D-JNKI-1 resulted in a significant decrease in the disease activity index (P = 0.013 for 1.0% DSS; P = 0.007 for 1.5% DSS). As a mild form of colitis was induced, histological examination did not show any distinct damage to the mucosa and crypts. However, expression of CD4+ and CD8+ cells was reduced in mice treated with D-JNKI-1 (not significant). Conclusion: Administration of D-JNKI-1 resulted in a clinical attenuation of chronic DSS colitis, and a therapeutic effect of D-JNKI-1 must therefore be assumed. The decrease in CD4+ and CD8+ cells may reflect the influence of D-JNKI-1 on T-cell activation, differentiation, and migration. Keywords: c-Jun N-terminal kinase inhibitor, dextran sulfate sodium colitis, inflammatory bowel diseases, T cell, D-JNKI-1